ChemInform Abstract: High Pressure Superconducting Phase of BI3: An ab initio Study. Issue 49 (9th December 2014) - Duan, Defang; Huang, Xiaoli; Chen, Changbo; Tian, Fubo; Bao, Kuo; Li, Da; Liu, Yunxian; Yu, Hongyu; Liu, Bingbing; Cui, Tian
Abstract The high pressure crystal structure of BI3 with space group P21/c consisting of B2I6 dimers is determined using an ab initio evolutionary algorithm for crystal structure prediction in conjunction with density functional theory.